(untitled) (American Journal of Islam and Society, 2003)
Decolonizing Methodologies, by Maori educationist Linda Tuhiwai Smith, challenges the dominant western "frameworks of knowledge." Many of the concerns voiced in this book are shared by Muslims, who also have been colonized both physically and intellectually. Thus, there is something for Muslim scholars to learn in the attempts of others to address western disciplines of knowledge. Smith argues that from the vantage point of the colonized, the term research is inextricably linked to European imperialism and colonialism. She points to the system and framework of how European research was carried out, classified, and presented back to the West, and then, through the eyes of the West, back to the colonized, a process that Edward Said has called "Orientalism." The alternative is to address social issues of indigenous peoples within the wider framework of self-determination, decolonization, and social justice in order to create "indigenous research, indigenous research protocols and indigenous methodologies" that relate to indigenous priorities and problems. This new framework and approach requires a historical and critical analysis of the role of research in the indigenous world so that it can provide alternatives as to how we see knowledge and its social construction, as well as methodologies and the politics of research ...